2016
DOI: 10.1073/pnas.1602360113
|View full text |Cite
|
Sign up to set email alerts
|

Reduced anthropogenic aerosol radiative forcing caused by biogenic new particle formation

Abstract: The magnitude of aerosol radiative forcing caused by anthropogenic emissions depends on the baseline state of the atmosphere under pristine preindustrial conditions. Measurements show that particle formation in atmospheric conditions can occur solely from biogenic vapors. Here, we evaluate the potential effect of this source of particles on preindustrial cloud condensation nuclei (CCN) concentrations and aerosol-cloud radiative forcing over the industrial period. Model simulations show that the pure biogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 51 publications
4
147
0
Order By: Relevance
“…4 Map of regions analysed in Table 1 and Fig. 7 not reflected in the model simulations above, is pure biogenic nucleation [100], which could increase PI CCN concentrations by 4-19% [101]. These changes are comparable to the standard deviations in CCN concentrations caused by 26 other processes and emissions so would constitute a significant change to the model.…”
Section: What Did Pre-industrial Aerosols Look Like?mentioning
confidence: 91%
See 2 more Smart Citations
“…4 Map of regions analysed in Table 1 and Fig. 7 not reflected in the model simulations above, is pure biogenic nucleation [100], which could increase PI CCN concentrations by 4-19% [101]. These changes are comparable to the standard deviations in CCN concentrations caused by 26 other processes and emissions so would constitute a significant change to the model.…”
Section: What Did Pre-industrial Aerosols Look Like?mentioning
confidence: 91%
“…The second major factor is the lower sink of nucleating vapours in the PI. Gordon et al [101] showed that this can allow nucleation of biogenic vapours [100] to increase substantially in the PI, providing a "nucleation buffering" mechanism that raises PI aerosol concentrations above the level that might be expected based on the generally lower emissions. A third factor is that the volatility of biogenic nucleating vapours depends on [38] which species were involved in the oxidation steps (ozone, OH, HO 2 , and NO 3 ) as well as the concentrations of NO x (ref [102]), which have been strongly affected by anthropogenic activities [103,104].…”
Section: Processes Controlling Pre-industrial Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though oxidized organics seem to be globally important for NPF (Jokinen et al, 2015;Gordon et al, 2016;, the formation of new particles by sulfuric acid and amines should still be considered because sulfuric acid-amine nucleation rates exceed those from oxidized organics as soon as the concentrations of the precursor gases (sulfuric acid and amines) are high enough . Therefore, at least locally or regionally, i.e., close to sources, amines should be relevant.…”
mentioning
confidence: 99%
“…Atmospheric aerosols are a widespread concern due to their physicochemical role in atmospheric processes, which can cause them to disturb the solar radiative balance of the earth (Bellouin et al, 2005;Gordon et al, 2016). The uncertainty regarding the radiative forcing induced by atmospheric particulate matter is a major obstacle to the accurate prediction of climate change (Kahn, 2012;Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%